Morfometría cráneo-mandibular y dentaria de tres especies de mamíferos de diferentes gremios tróficos. Loreto, Perú - Galvez Chamorro, Cesar Samuel (2025)
The present study was carried out using skull specimens housed in the Zoology Museum of the Faculty of Biological Sciences. Its aim was to evaluate cranio-mandibular and dental morphometric parameters among three mammalian species representing different trophic guilds: Cuniculus paca (herbivore), Nasua nasua (omnivore), and Leopardus pardalis (carnivore). The study began with the development of three independent morphometric protocols that differed in parameters depending on the species studied. A total of 25 skulls of C. paca (80 parameters), 34 of N. nasua (91), and 16 of L. pardalis (73) were analyzed. The results showed that C. paca exhibited specific developments in the molar regions and structures related to the processing of fibrous food. N. nasua displayed a combined morphology, while L. pardalis stood out for its carnivorous specialization, reflected in high measurements of canines, mandibular processes, and premolars. The Principal Component Analysis (PCA) distinguished the three species according to their trophic guild, with significant segregation in morphometric space and no relevant overlaps. In conclusion, cranio-mandibular morphology is strongly associated with diet, and morphometry can provide relevant information to interpret functional adaptations in Amazonian mammals. Overall, this study contributes to the understanding of ecological interactions between species and provides useful tools for wildlife management and conservation.